Study of Iktiofauna Biodiversity Based on Geographical Information Systems (GIS) in the Progo River, Magelang, Central Java - Jailani, Abdul Qadir; Mujtahidah, Tholibah (Journal of Aquaculture Science, 2021)
The study of biodiversity is important in looking at the current condition of an aquatic environment. The purpose of this study is to examine the biodiversity of the fauna in the Progo River in determining the level of fish diversity and the status of fish resources in the Progo river by using a Geographical Information System (GIS). The sampling method was carried out by purposive sampling consisting of 17 stations. The data taken includes coordinate points, the diversity index (H '), evenness index (E), dominance index (D), and relative abundance (Kr), as well as making a map of the distribution of progo river fish using Arcgis software version 10.5. The results showed that the diversity index value (H ') was moderate to high with a value range of 2.24 to 3.83, with a catch composition consisting of 23 species and 11 families. The evenness index value (E) of the progo river ranges from 0.71 to 1.21. Based on this value, the Progo River has an evenness value between species that is relatively even or the number of individuals of each species is relatively the same. Progo river dominance index value ranges from 0.002-0.008, that is, no fish species dominates. The highest relative abundance (Kr) was balar fish (Barbonymus balleroides) = 0.12%, melem fish (Osteochilus vittatus) = 0.11%, uceng fish (Nemacheilus fasciatus) 0.09%, tilapia fish (Oreochromis niloticus) 0 , 08%, while the lowest was kekel fish (Glyptothorax platypogon) and sepat fish (Trichopodus trichopterus) with a value of 0.01%. The results of the analysis of the distribution of fish in the Progo river show that the fish are widely distributed in the river area which has deep and calm water characteristics, this is indicated by the number of catches at each research station. Keywords: Biodiversity, Progo River, Geographical Information System (GIS)